Plant Physiological Ecology - Lambers, Hans (Springer, 2017)
For a variety of reasons, the prospects for managing change seem better in agriculture than in forests or in wild plant communities. It is possible to intervene dramatically in the normal process of evolutionary change by genetic manipulation. Extensive screening of random mutations in a target species such as Arabidopsis thaliana can reveal genes that allow plants to survive rather simplified stress tests. This is but the first of many steps, but eventually these will have their impact, primarily on agricultural and industrial crops. There is a huge research effort in this area and much optimism about what can be achieved. Much of it is done with little reference to plant physiology or biochemistry and has a curiously empirical char-acter. One can sense that there is impatience with plant physiology that has been too slow in defining stress tolerance, and a belief that if a gene can be found that confers tolerance, and it can be transferred to a species of interest, it is not of primev importance to know exactly what it does to the workings of the plant. Such a strategy is more directed toward outcomes than understanding, even though the technology involved is sophisticated. Is there a place for physiological ecology in the new order of things? The answer is perhaps a philosophical one. Progress over the centuries has depended on the gradual evolution of our understanding of fundamental truths about the universe and our world. Scientific discovery has always relished its serendipitous side but had we been satisfied simply with theoutcomes of trial and error we would not be where we are today.